Consumers' perceived relationship between television advertising recall and brand purchase decision - Siew, Siok Peik (1999)
When a customer chooses a certain brand, many factors actually influence this purchasing decision. Marketers would very much like to attribute this to advertising, but other factors like distribution, packaging, price, etc., may actually influence this purchase. However, television is a very obvious medium in this age and what makes it more unique and stimulating than other media is the moving images that the viewer can see and hear, With constant exposure, a certain level of recall should be expected for a brand. Recall, in addition to other factors and not solely by itself, may influence the brand purchasing decision of consumers. As such, the purpose of this research is to determine if there is any significant relationship between recall of television advertising and brand purchase decision. It also examines if the consumer's level of involvement with the brand has any bearing on recall of its advertising. The level of involvement can be understood by the degree of personal relevance or importance. In addition, the study considers if personal influences like social-demographic factors have any bearing on the relationship between recall and brand purchase decision. It also seeks to explain what are the factors that influence recall of an ad. For the study, 145 respondents residing in the Klang Valley were surveyed using self-administrated, drop-and-pick questionnaire. The questionnaire measured the respondents' recall level, involvement level, buying intention and contains social-demographic factors questions. Majority of the respondents was single, Chinese females aged between 21 - 35 years. Most of them attained a Bachelor's Degree, worked in professional/management capacities and earned between RM1,500 - RM3,000 a month. Using the Chi-square test and linear regression, the results show that there is a significant relationship between TV advertising recall and brand purchase decision, but the influence of recall on brand purchase decision is very weak. This indicates that recall may not be the sole cause of this relationship. Other factors not covered in the study at hand may impact on the relationship. Linear regression analysis show that the relationship is more significant for respondents in the high involvement group, and this is not so for those in the low involvement group. The findings of multiple linear regression also support the contention that the executional style (message content, product content and brand characteristics) of an ad does impact commercial effectiveness as measured by recall. Lastly, the Chi-square tests show that brand purchase decision has a relationship with the respondents' age, marital status, race and gross monthly income.